Efeitos da sobrecarga calórica em ratos machos submetidos ou não a restrição protéica in útero - Rizzi, Victor Hugo Gonçalves [UNESP] (2014)
Background. Prior studies show that maternal protein-restricted offspring (LP) have pronounced reduction of nephron number and arterial hypertension associated with unchanged glomerular filtration rate and enhanced glomerular area that may be related with glomerular hyperfiltration/overflow and account for the glomerular filtration barrier breakdown and early glomerulosclerosis. Additionally, evidence is emerging that highlights the far-reaching consequences of high fat diet (HFD) on kidney morphology and function disorders. The present study aims to evaluate the effect of HFD on renal function and morphology in LP rats. Methods. Maternal protein-restricted offspring (LP, 6% casein) and normal protein intake rats (NP, 17% casein) were submitted to ingestion of HFD (LPH and NPH, respectively) or standard chow to rodents (LPN and NPN) from 8th to 13th of age. Renal Function, systemic arterial pressure, immunohistochemistry and scanning electron microscopy were performed and biochemical serum parameters analyzed. Results. The body adiposity and mass were reduced in LPN which in turn, increased in NPH and LPH groups. Striking increased in total cholesterol was observed in NPH and LPH, and increased LDL in LPH. The blood pressure was significant increase in LPH groups from the 10th and 12th week of life compared to the other groups. A reduced urinary excretion of sodium was observed in low-protein treated rats while NPH and LPH animals presented an increased urinary acidification in time-dependent fashion. The LPN, NPH and LPH groups showed an increased expression of AT1r, transforming growth factor (TGFβ-1), collagen and fibronectin. By ultraestructural analysis we found a pronounced enfacement of foot process in treated groups and HFD-treated offspring showed wear-out of podocytes by rupture of cell membranes. In parallel all treated rats present a significant urinary protein excretion. Conclusion. In conclusion, from our present ...